Numerical study on the surface evolution and flow dynamics in laser polishing of 100Cr6 steel based on the coupled capillary and thermocapillary flow - Chuqiao Fang; Wei Dai; Xiao Wu; Sijin Wang (AIP Advances)
Laser polishing (LP) has gained widespread interest in various engineering fields due to its high efficiency, precision, and non-contact processing capabilities. Despite its potential applications, most LP research primarily relies on experimental approaches, which are time-consuming, expensive, and may not systematically reveal the underlying mechanisms of laser–material interactions. Therefore, integrating numerical simulation techniques is crucial for enhancing our understanding and optimizing the LP process. This study develops a two-dimensional transient numerical model to simulate the superficial surface evolution during the LP of 100Cr6 steel. A moving laser beam with a top-hat energy density distribution was implemented, considering the microscopic flow mechanism of the molten pool through combined capillary and thermocapillary flows. A detailed analysis of temperature distributions, molten pool behaviors, and surface profiles was conducted to assess how various process parameters influenced the results. The simulation results indicated that an optimal surface roughness of approximately Ra 0.706 µm can be achieved using the optimized parameters (laser power: 400 W, scanning speed: 300 mm/s, and laser beam size: 300 μm). Additionally, the molten pool can form within a suitable temperature and time range for LP using these optimized parameters. The results also indicated that the LP surface roughness exhibits a V-shaped relationship with laser power, scanning speed, and laser beam size. This study highlights the critical role of thermal input in LP and discusses how adjusting laser process parameters effectively controls this input. It provides numerical simulation parameters and theoretical guidance for LP research, ultimately leading to desired polishing effects.